Pain in the Foot: Pathogenesis, Diagnosis and Treatment - Yatskevych A. (Львівський клінічний вісник)
Introduction. Deformation and foot pain are significant causes of the patient’s medical care. The pain in the foot combined with the violation of its structure is the basic indicators for the operational treatment in about one third of patients in orthopedic hospitals. The effectiveness of its treatment is insufficient, there is a tendency to chronization of the processes often followed by relapses. For the effective choice of the treatment metod it is important to determine the cause, pathogenesis, the origin of the pain impulses, and a direct impact on the source of pain. So, there are four groups of lesions of patients following the predominant localization of pain in the foot: with pain in the anterior part of the foot; with pain in the medial part of the foot; with pain in the lateral part of the foot; with pain in the back of the foot. The respective etiological and pathogenetic situations are characteristic for each of these groups. Aim. To characterize the pathogenesis, diagnoses altogether and treatment of pain in the foot. Materials and methods. Content analysis, method of system and comparative analysis, bibliosemantic method of study of the actual scientific researches on the topic of the pain in the foot, its pathogenesis, diagnose algorithm and treatment with the demonstration of a clinical case have been used. Results. Surgical intervention may be used in case of the ineffectiveness of conservative foot pain treatment, which includes reduction of physical activity, treatment of nonsteroidal anti-inflammatory drugs, local administration of glucocorticosteroids, biologic drugs and matching of footwear. In case of conservative treatment, along with anti-inflammatory drugs, sharp stresses on the Achilles tendon, stretching of the calf muscles should be excluded. Local injecting treatment is effective using biologic drugs and glucocorticosteroids, which can be administered exclusively in the vagina, rather than in the tendon. For the insufficient efficacy of conservative treatment, such operations as longitudinal excision of the degenerate shaft of the tendon that preserves its integrity in the absence of thickening and, consequently, stenosis in the vagina, endoscopic dermatitis are recommended. The choice of operative technique is quite wide – from the removal of bursa, the debridement of the Achilles tendon enthesion to the resection of the osteophytes of the heel hump with the reinsertion of the tendon and prolonged rehabilitation. Conclusions. The causes and pathogenetic mechanisms of pain in the foot are extremely diverse, the patterns of their occurrence and the combination are insufficiently studied. Accordingly, the effectiveness of treatment remains low. Thus, there is a need for further improvement of the ways of diagnosis and supervision of patients with pain in the foot.